Bumbay, kulambo and five-six: Narratives on the formation of a Sikh community in the Philippines - Espeña, Darlene Machell de Leon (Animo Repository, 2022)
This study focuses on the narratives of Sikh migrants in the Philippines from India’s independence in 1947 up to the turn of the century. There are two distinct groups of Indian migrants in the Philippines, the Sindhis and the Punjabis. The Sindhis are mostly Hindus from the province of Sindh while Punjabis are predominantly Sikhs from Punjab. The two groups are not only divergent in religion. Each of them has a distinct language, tradition and culture. Each of them has their own ways of adapting to the local culture. The author chose to concentrate on the Sikhs because of their closer interaction with the locals as money lenders and retail store owners. They managed to learn how to speak Filipino more fluently and are more exposed to local culture and yet they managed to preserve their distinct “Indian-ness.” The present study explores and assesses the various factors that motivated the Sikhs to move out of the land of their birth particularly when the province Punjab was divided between India and Pakistan. Furthermore, it evaluates how Indians respond to the local culture and traditions and how they deal with the impediments of migrant life in the country. It delves into the processes of how the Sikhs transmit as well as maintain their culture and how modernity and globalization affect their decisions to stay and their adaptations to line in a land far from the country they might still call home. The author asserts that the social and economic conditions in Punjab after the partition of India and Pakistan were the push factors that motivated the Sikhs to migrate and try their luck in strange lands. Upon reaching the Philippines, the Sikhs had to cope with the local culture and produce a simulation of life in the home country albeit with perceptible deviations. They utilized the benefits of globalization and modernity to modify the limited space they occupy to transplant “India” within the Philippines. From the Indian specialty stores to the Sikh temple they built, the food they eat, songs they patronize and clothes they wear, the Sikhs reinforce Indian culture and re-created Indian life in the country. India, or the concept by which the Sikhs view India, can now be easier to imagine, visualize and experience despite geographic dislocations. Throughout their long history of residing in the Philippines, the Sikhs managed to uphold the most vital aspects/necessities of life back in India (perhaps even better) and for this reason, they opted to remain in a country far beyond the boundaries of their own home.